Herpesvirus Saimiri Transforms Human T-Cell Clones to Stable Growth without Inducing Resistance to Apoptosis - Kraft, Michael S. (American Society for Microbiology, 1998)
Herpesvirus saimiri (HVS) transforms human T cells to stable growth in vitro. Since HVS codes for two different antiapoptotic proteins, growth transformation by HVS might be expected to confer resistance to apoptosis. We found that the expression of both viral antiapoptotic genes was restricted to cultures with viral replication and absent in growth-transformed human T cells. A comparative examination of HVS-transformed T-cell clones and their native parental clones revealed that the expression of Bcl-2, Bcl-X(L), Bax, and members of the tumor necrosis factor receptor (TNF-R) superfamily with a death domain, namely, TNF-RI, CD95, and TRAMP, were not modulated by HVS. Expression of CD30 was induced in HVS-transformed T cells, and these cells also expressed the CD30 ligand. Uninfected and transformed T cells were sensitive to CD95 ligation but resistant to apoptosis mediated by TRAIL or soluble TNF-α. CD95 ligand was constitutively expressed on transformed but not uninfected parental T cells. Both cell types showed similar sensitivity to cell death induction or inhibition of T-cell activation mediated by irradiation, oxygen radicals, dexamethasone, cyclosporine, and prostaglandin E(2). Altogether, this study strongly suggests that growth transformation by HVS is based not on resistance to apoptosis but, rather, on utilization of normal cellular activation pathways.